Evaluation of Effective Connectivity Between Brain Areas Activated During Simulated Driving Using Dynamic Causal Modeling - Choi, Mi-Hyun; Kim, Hyung-Sik; Chung, Soon-Cheol (Frontiers in Behavioral Neuroscience, 2020)
This study was examined the effective connectivity between brain areas activated during driving. Using a driving simulator, the subjects controlled a wheel with both of their hands as well as an accelerator and brake pedal with their right foot. Of the areas activated during driving, three areas from each hemisphere were analyzed for effective connectivity using dynamic causal modeling. In the right hemisphere, bidirectional connectivity was prominent between the inferior temporal gyrus, precuneus, and lingual gyrus, which provided driving input . In the left hemisphere, the superior temporal gyrus provided driving input, and bidirectional connectivity was prominent between the superior temporal gyrus, inferior parietal lobule, and inferior frontal gyrus. The visual attention pathway was activated in the right hemisphere, whereas the inhibitory control movement and task-switching pathways, which are responsible for synesthesia, were activated in the left hemisphere. In both of the hemispheres, the visual attention, inhibitory control movement, and episodic memory retrieval pathways were prominent. The activation of these pathways indicates that driving requires multi-domain executive function in addition to vision. Moreover, pathway activation is influenced by the driving experience and familiarity of the driver. This study elucidated the overall effective connectivity between brain areas related to driving.